Glimmer of a new Leviathan total war in the realism of Niebuhr, Morgenthau, and Waltz - Craig, Campbell (Columbia University Press, 2003)
Presents the story of how the three chief architects of an influential ideology struggled with the implications of their own creation. This book offers historical context for contemporary debates about weapons of mass destruction and the post-Cold War international order.